Metformin Use and Prostate Cancer Risk - Preston, Mark A.; Riis, Anders H.; Ehrenstein, Vera; Breau, Rodney H.; Batista, Julie L.; Olumi, Aria F.; Mucci, Lorelei A.; Adami, Hans-Olov; Sørensen, Henrik T. (European urology, 2014)
Metformin may decrease prostate cancer (PCa) risk by reducing hyperinsulinemia-associated carcinogenesis or through direct effects on cancer cells. To evaluate the association between metformin use and PCa diagnosis. We used the Danish Cancer Registry and the Aarhus University Prescription Database to conduct a nested case–control study among men residing in northern Denmark from 1989 to 2011. We identified 12 226 cases of PCa and used risk-set sampling to select 10 population controls per case (n=122 260) from among men alive on the index date and born in the same year. A sensitivity analysis was conducted using subjects who had prostate-specific antigen (PSA) testing prior to 1 yr before the index date. Metformin exposure was assessed using prescriptions redeemed before the index date. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using logistic regression. The association between metformin use and PCa diagnosis was determined, controlling for diabetes severity and other potential confounders. Metformin users were at decreased risk of PCa diagnosis compared with never-users (adjusted OR [aOR]: 0.84; 95% CI, 0.74–0.96). Diabetics on no medication (aOR: 0.98; 95% CI, 0.89–1.09) or on other oral hypoglycemics (aOR: 0.98; 95% CI, 0.86–1.10) did not have a reduced risk of PCa, while users of insulin did have a reduced risk (aOR: 0.77; 95% CI, 0.64–0.93). In the PSA-tested group, metformin use was associated with decreased risk of PCa compared with nonuse (aOR: 0.66; 95% CI, 0.51–0.86). Diabetics on no medication (aOR: 1.03; 95% CI, 0.86–1.24), diabetics on other oral hypoglycemics (aOR: 0.92; 95% CI, 0.70–1.20), and insulin users (aOR: 0.83; 95% CI, 0.56–1.24) did not have a statistically significant reduced risk of cancer. Metformin use was associated with decreased risk of PCa diagnosis, whereas diabetics using other oral hypoglycemics had no decreased risk. We studied the relationship between metformin (a diabetic medication) and prostate cancer in Denmark. We found that metformin reduced the risk of prostate cancer diagnosis, whereas other oral antidiabetic medications did not. A nested case–control study was conducted using Danish population-based registries to investigate the relationship between the antidiabetic medication metformin and prostate cancer. Metformin use was associated with a reduced risk of prostate cancer diagnosis, whereas the use of other oral antidiabetic medications was not.